Zinc Binding Properties of Engineered RING Finger Domain of Arkadia E3 Ubiquitin Ligase - Christos T. Chasapis; Ariadni K. Loutsidou; Malvina G. Orkoula; Georgios A. Spyroulias (Bioinorganic Chemistry and Applications)
Human Arkadia is a nuclear protein consisted of 989 amino acid residues, with a characteristic RING domain in its C-terminus. The RING domain harbours the E3 ubiquitin ligase activity needed by Arkadia to ubiquitinate its substrates such as negative regulators of TGF-𝛽 signaling. The RING finger domain of Arkadia is a RING-H2 type and its structure and stability is strongly dependent on the presence of two bound Zn(II) ions attached to the protein frame through a defined Cys3-His2-Cys3 motif. In the present paper we transform the RING-H2 type of Arkadia finger domain to nonnative RING sequence, substituting the zinc-binding residues Cys955 or His960 to Arginine, through site-directed mutagenesis. The recombinant expression, in Escherichia coli, of the mutants C955R and H960R reveal significant lower yield in respect with the native polypeptide of Arkadia RING-H2 finger domain. In particular, only the C955R mutant exhibits expression yield sufficient for recombinant protein isolation and preliminary studies. Atomic absorption measurements and preliminary NMR data analysis reveal that the C955R point mutation in the RING Finger domain of Arkadia diminishes dramatically the zinc binding affinity, leading to the breakdown of the global structural integrity of the RING construct.